Edge effects impact blue carbon dynamics across coastal ecotones in a tropical seascape - Yando, Erik S. (2025)
Coastal wetlands are important for their ability to regulate global climate through the sequestration and long-term storage of carbon. Accurate quantification of ecosystem-specific carbon dynamics (including sequestration, storage, and fluxes) is needed to develop accurate carbon budgets that inform climate change mitigation. Most work to quantify carbon dynamics either use subsampling in core habitats or benefit transfers to upscale values. While these approaches are valuable, our understanding of carbon dynamics across ecosystem transitions and overall heterogeneity remains a critical gap in coastal ecosystems as boundaries are not always clear. In this study, we established transects across both mangrove and seagrass ecotones into adjacent tidal flats in Singapore to quantifying vegetation cover, soil carbon storage, and CO2 fluxes. Vegetation cover in all transitions and soil carbon storage in most transitions followed a decreasing sigmoidal pattern from vegetated to unvegetated portions, but differed in rate and width. CO2 fluxes followed a peak distribution in mangrove–tidal flat transitions with maximum values occurring within the mangroves and were correlated with pneumatophore density, while seagrasses saw a linear increase in CO2 fluxes from the seagrass to tidal flat. Seascape analysis of soil carbon showed site-specific impacts that resulted in differences in carbon stocks (0%–8%) as well as the width of these transitions. This study highlights the importance of understanding ecotones to better account for edge effects, which can lead to the over or under estimation of carbon, and provides a needed step in increasing the accuracy of blue carbon assessments in these critical ecosystems.